Social Housing and the Minha Casa Minha Vida Program - range 1: environmental issue in housing production - Nunes de Sousa, Isabel Cristina [UNESP]; Braga, Roberto [UNESP] (Pontificia Univ Catolica Parana-pucpr, 2020)
This work aimed to incorporate an environmental viewpoint into the social housing discussion through the urban insertion analysis of the housing complexes produced by the PMCMV. Therefore, it sought to understand how the demands of social housing dialogue with environmental protection. Thus, it was analyzed the link between the implementation of the first range PMCMV housing developments in a medium-sized city in the State of Sao Paulo, and its environmental and socio-spatial effects. It aimed to contribute to the discussions on the social housing provision process, from an environmental perspective, linking the physical conditions to city production strategies. Through a case study, it was identified an increase in the occupation of improper environmental areas, due to housing provision via public financing. This reveals a detachment between social and environmental function, as well as urban and housing policies.
Keywords: Mass-housing complexes; Environmental fragilities; Urban instruments; Urban voids; Housing policy